A psicologia da educação na formação docente - Vercelli, Ligia de Carvalho Abões (2007)
The aim of this research is to know the senses that students in Pedagogical formation attribute to the studied knowledge of psychology in discipline Educational Psychology. The investigation followed the methods of qualitative research, making use of a research instrument called Version of Senses, definied as a free report that does not inted to be an objective registry about what happened, but it is a lived reaction to it. It may be written or spoken imeddiately after what occorred and it is an expreessive speech about the author s immediate experience considering a recently finished meeting. In this perspective, it was asked student/teachers that, at the end of each meeting, they should write the senses provocated by the contents treated in the class, its favourable aspects and how it could help the schooling work. This instrument was applied to five students/teachers while they took the course of Educational Psychology part I and II. The analysis of the sense of their experiences showed four themes: 1) contributions of Educational Psychology for pedagogical practices, 2) thinking and reflection about the adolecent student. 3) reflection and search for changing the pedagogical practice and 4) understanding of a manhood view.It was concluded that, though all the students/teachers agreed that the Educational Psychology subject contributes with their pedagogical practice, they did not achieve a clear explanation to its real contributions in everday routine in school, they made use of a common sense language, which indicates that did not happen a knowledge appropriation. They also showed a certain difficulty of understandig adolecent students and said that it is fundamental to study this matter because they work with people at this age. They emphasized that to reflect about the everyday classroom problems makes the class to become even more interesting and that, in this way, the theory learned brings effects to the pedagogical practice. They also emphasized how important it is to undestand each student in a whole sense.